A recapitulation of rotavirus and reinforcement of the need for vaccination - Menda, Manoj Kumar; Anvekar, Priyanka; Abbasi, Zainab (International Journal of Endorsing Health Science Research, 2019)
In 1973, Ruth Bishop discovered Rotavirus, its clinical impacts and public health significance were vastly underrated especially in developed countries. Rotavirus is a double-stranded Ribonucleic Acid (RNA) virus which belongs to the Reoviridae family. So far 10 species (A-J) of this virus have been discovered amongst which Rotavirus A is the most common, that is associated with human infections. Rotavirus diarrhea is a leading cause of under 5-year mortality in children. Several studies have attributed 440,000 deaths in children under 5 years of age.